2022
DOI: 10.1248/bpb.b22-00170
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Skin Injury Risk Caused by Extravasation of Electrolyte Solutions or Infusions in a Rat Model

Abstract: Cytotoxic agents are classified according to the severity of skin injury after extravasation. However, injuries caused by extravasation of noncytotoxic agents have not been sufficiently investigated, although the risk of extravasation is mentioned in medical safety information published by the Japan Council for Quality Health Care. Therefore, in this study, we focused on noncytotoxic electrolyte solutions and infusions and evaluated skin injuries during leakage using extravasation model rats. Rats were anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Several studies have reported skin injuries caused by PPN extravasation. In a previous study on laboratory animals, Taogoshi et al4 reported that PPN extravasation resulted in significant changes, such as erythema and induration, but not in histopathological changes, such as necrosis, making PPN comparable to irritants. In contrast, Ersoy and Tasargol23 examined an intensive care unit patient with a cardiac disease and reported a case of refractory skin necrosis and bullous skin lesions caused by PPN extravasation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Several studies have reported skin injuries caused by PPN extravasation. In a previous study on laboratory animals, Taogoshi et al4 reported that PPN extravasation resulted in significant changes, such as erythema and induration, but not in histopathological changes, such as necrosis, making PPN comparable to irritants. In contrast, Ersoy and Tasargol23 examined an intensive care unit patient with a cardiac disease and reported a case of refractory skin necrosis and bullous skin lesions caused by PPN extravasation.…”
Section: Discussionmentioning
confidence: 98%
“…25 Calcium chloride extravasation is attributed to calcium calcification. In a laboratory animal study, Taogoshi et al 4 suggested that calcium chloride extravasation causes tissue necrosis and phlebitis, making the properties of calcium chloride comparable to those of vesicants. Also, Lin et al 26 studied patients who had postoperative hypocalcemia after parathyroidectomy and reported 4 cases of injection site skin injuries caused by calcium chloride administration.…”
Section: Calcium Chloridementioning
confidence: 99%
See 2 more Smart Citations
“…In our patient, the severe and large ulceration healed within 11 months after careful wound care leaving a large scar under the breast. No skin biopsies were taken, but skin necrosis and prolonged ulceration after calcium chloride infusion is usually caused by tissue calcification (calcinosis cutis) ( 25 ). This serious side effect has not previously been reported after CaEP and was not seen in other patients during the study.…”
Section: Discussionmentioning
confidence: 99%